Involvement of Cytochrome P-450 in the Biosynthesis of Dhurrin in Sorghum bicolor (L.) Moench - Halkier, Barbara Ann (1991)
The biosynthesis of the tyrosine-derived cyanogenic glucoside dhurrin involves N-hydroxytyrosine, (E)- and (Z)-p-hydroxyphenylacetaldehyde oxime, p-hydroxyphenylacetonitrile, and p-hydroxymandelonitrile as intermediates and has been studied in vitro using a microsomal enzyme system obtained from etiolated sorghum (Sorghum bicolor [L.] Moench) seedlings. The biosynthesis is inhibited by carbon monoxide and the inhibition is reversed by 450 nm light demonstrating the involvement of cytochrome P-450. The combined use of two differently prepared microsomal enzyme systems and of tyrosine, p-hydroxyphenylacetaldehyde oxime, and p-hydroxyphenylacetonitrile as substrates identify two cytochrome P-450-dependent monooxygenases: the N-hydroxylase which converts tyrosine into N-hydroxytyrosine and the C-hydroxylase converting p-hydroxyphenylacetonitrile into p-hydroxymandelonitrile. The inhibitory effect of a number of putative cytochrome P-450 inhibitors confirms the involvement of cytochrome P-450. Monospecific polyclonal antibodies raised toward NADPH-cytochrome P-450-reductase isolated from sorghum inhibits the same metabolic conversions as carbon monoxide. No cytochrome P-450-dependent monooxygenase catalyzing an N-hydroxylation reaction has previously been reported in plants. The metabolism of p-hydroxyphenylacetaldehyde oxime is completely dependent on the presence of NADPH and oxygen and results in the production of p-hydroxymandelonitrile with no accumulation of the intermediate p-hydroxyphenylacetonitrile in the reaction mixture. The apparent NADPH and oxygen requirements of the oxime-metabolizing enzyme are identical to those of the succeeding C-hydroxylase converting p-hydroxyphenylacetonitrile to p-hydroxymandelonitrile. Due to the complex kinetics of the microsomal enzyme system, these requirements may not appertain to the oxime-metabolizing enzyme, which may convert p-hydroxyphenylacetaldehyde oxime to p-hydroxyacetonitrile by a simple dehydration.